PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 001 RANTAU PANJANG KIRI KECAMATAN KUBU BABUSSALAM - Jumidar '; Hendri Marhadi; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated to learn mathematics is still low yields siswa.Hasil mathematics learning is still relatively low and has not reached the classical completeness. The research was conducted from April 25 2016 to May 9th, 2016. The subject of this study is the fourth grade students of SDN 001 Rantau Panjang Kiri was 22 people, 15 men and 7 women. The instrument of this research is a learning device that consists of a syllabus, lesson plans, worksheets and evaluation. Data collection instrument in this study was the observation sheet and achievement test. While data collection techniques are observation, tests and documentation techniques. The increase in the percentage of teachers in each cycle of activity, which in the first cycle 1 meeting is 64.29% with both categories, at the meeting of 2 increased to 75.00% in both categories. While the teacher activity in the second cycle 3 meeting is 85.71% with very good categories and at the meeting of 4 increased to 92.86% with the category very well. Increasing the percentage of student activity during each cycle, where the first cycle of meetings 1 is 57.14% with enough categories and meeting 2 is 67.86% with both categories. While the activities of students in the second cycle is 78.57% 3 meeting with both categories and 4 meeting increased to 89.28% with the category very well. The average student learning outcomes from basic score 64.23 increased to 73.86 in the first cycle with the increase of daily keulangan I base score of 15.00%. In the second cycle again experienced an average increase learning outcomes become Deuteronomy 81.59 on Day 2, the increase of the daily keulangan II base score of 27.03%. The percentage of classical completeness base score of 36.36% with a category Not Completed, increased in Deuteronomy Daily Cycle I to 77.27% with the category Not Completed. Then in Deuteronomy Daily Cycle II increased to 86.36% with category l Completed. It can be concluded that the hypothesis proposed in this study received. In other words, the application of the approach Contextual Teaching and Learning (CTL) can improve learning outcomes mathematics second semester of fourth grade students of SDN 001 Rantau Panjang Kiri Babussalam Kubu district. Key Words: Learning Model CTL, Mathematics Learning Outcomes